2023
DOI: 10.3390/foods12183470
|View full text |Cite
|
Sign up to set email alerts
|

Egg White and Yolk Protein Atlas: New Protein Insights of a Global Landmark Food

Eleana Sarantidi,
Alexandra Ainatzoglou,
Christine Papadimitriou
et al.

Abstract: (1) Background: The chicken egg is an animal product of great agronomic interest. The egg white and yolk constitute high-quality protein sources for humans with high digestibility and well-balanced amino acid profiles. Despite the egg white and yolk protein’s undisputed value, research to unravel their full proteome content and its properties is still ongoing. We aimed to exhaustively analyze the proteome of egg white and yolk by applying intrinsic proteomics and bioinformatics approaches in order to unravel t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Among all the available literature on egg white and egg yolk, Sarantidi et al [ 2 ] recently reported the highest number of proteins, 398 and 456, respectively, identified through an LC–MS/MS intrinsic design. The most abundant proteins found in egg white are ovalbumin (54.0%), followed by ovotransferrin (12.0–14.0%), ovomucoid (11.0%), ovomucin (3.5%) and lysozyme (3.4–3.5%), while few other minor proteins, such as ovoinhibitor, ovoglycoprotein, ovoflavoprotein, ovomacroglobulin (also known as ovostatin), cystatin and avidin, are present in low percentages of 0.05–1.5% [ 1 , 4 , 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among all the available literature on egg white and egg yolk, Sarantidi et al [ 2 ] recently reported the highest number of proteins, 398 and 456, respectively, identified through an LC–MS/MS intrinsic design. The most abundant proteins found in egg white are ovalbumin (54.0%), followed by ovotransferrin (12.0–14.0%), ovomucoid (11.0%), ovomucin (3.5%) and lysozyme (3.4–3.5%), while few other minor proteins, such as ovoinhibitor, ovoglycoprotein, ovoflavoprotein, ovomacroglobulin (also known as ovostatin), cystatin and avidin, are present in low percentages of 0.05–1.5% [ 1 , 4 , 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chicken eggs have an undisputedly high biological value, being a good source of various macro- and micro-nutrients. The high nutritional value of the eggs is due to the high content of proteins with an ideal amino acids profile, essential lipids, vitamins and minerals [ 1 , 2 ]. These components are not evenly distributed between the egg components: the egg yolk consists of 55.00% water, 26.70% fats, 15.50% proteins, 1.68% ash and 1.09% carbohydrates, while the egg white has significantly higher amounts of water (87.60%) and significantly lower contents of proteins (10.80%), fats (0.19%), ash (0.62%) and carbohydrates (0.85%) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hen egg proteins have high digestibility and absorption rates, and are called complete proteins [ 3 ]. Proteomic analyses identified 371, 428, and more than 500 proteins in egg white, yolk, and eggshell membrane proteins, respectively [ 4 , 5 ]. Egg white proteins mainly include ovalbumin, ovotransferrin, ovomucin, ovomucoid, and lysozyme [ 6 ].…”
Section: Introductionmentioning
confidence: 99%